2014
DOI: 10.3109/01913123.2014.888112
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulopathy in Adult Recipients of Pediatric Kidneys

Abstract: To compare "for cause" renal biopsies (bx) from adult recipients of pediatric-donor kidneys (PDK) versus adult-donor kidneys (ADKs), we reviewed 103 graft bx from 50 PDK recipients and 85 bx from 49 ADK recipients. PDK bx displayed more frequent glomerular pathology with immune complex-mediated glomerulonephritis present in 11/103 PDK versus 1/85 ADK (p < 0.05). In 15/103 PDK bx and 1/85 ADK (p = 0.001), the association of glomerular sclerosis, expanded mesangium, and halo of prominent podocytes by light micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…Compared to diffuse AS-like GBM change reported by Nadasdy et al, 20 only 3 cases in our series showed diffuse lesion, while the other 4 only segmental. Choung and Meleg-Smith 15 described that PDG affected GBM mainly on the epithelial side, external lamina rara, while in our series both the internal and external lamina rara were thickened.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Compared to diffuse AS-like GBM change reported by Nadasdy et al, 20 only 3 cases in our series showed diffuse lesion, while the other 4 only segmental. Choung and Meleg-Smith 15 described that PDG affected GBM mainly on the epithelial side, external lamina rara, while in our series both the internal and external lamina rara were thickened.…”
Section: Discussioncontrasting
confidence: 41%
“…Four of the 6 grafts developed dysfunction after 3 months to 3 years posttransplantation, and in all cases AS was excluded. In 2014, Choung and Meleg-Smith 15 reported a unique lesion of the glomerular in pediatric grafts transplanted into adults identifiable on electron microscopy, and named the lesion PDG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ size mismatch, i.e., typically a too-small-forbody-size transplant as a cause for allograft dysfunction, proteinuria, and glomerular remodeling was first described by Truong et al in 1991 [7]. Truong's observations were subsequently further characterized by Nadasdy et al and Choung et al [8,9], reporting glomerulopathies in 9% of adult patients receiving donor kidneys from patients younger than 10 years of age. The authors described marked alterations of the glomerular filtration barrier very similar to the currently made observations.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Despite the comparable long-term outcome concerning glomerular filtration rate (GFR) in these recipients, there are scarce data about development of hyperfiltration injury in these small pediatric donors, especially focusing on proteinuria and histological changes. 17 , 18 Of note, surveillance biopsies were not performed routinely.…”
Section: Introductionmentioning
confidence: 99%